Desire of recognition: american beauty in the light of Hegel - Menk, Tomas Farcic (2018)
With this paper, we aim to discuss the movie American Beauty under the light of the Hegelian philosophy or, more specifically, of the so-called dialectic of the master and the slave. To accomplish this task, we divided our text into three moments: 1 - we analyze some aspects relating to how the relationship among one's consciousnesses of oneself is established in life, creating dominance (lord) and subordination (slave) relations in intersubjectivity relations. The contrast between the two elements determines that, in order to achieve recognition, a consciousness must subdue the other according to its will, that is, one will is recognized (that of the master) whereas the other is the recognizer (that of the slave). 2 - we present central elements of the film as the background for our analysis. 3 - we critically discuss the film based on the conceptual elements presented in item one, demonstrating to what extent the film can be understood as an attempt by the protagonist to overcome the total indifferentiation, to establish a life and death struggle, and finally to be recognized in his desires.